2008
DOI: 10.1051/0004-6361:200809810
|View full text |Cite
|
Sign up to set email alerts
|

The accretion mechanism in low-power radio galaxies

Abstract: We study a sample of 44 low-luminosity radio-loud AGN, which represent a range of nuclear radio-power spanning 5 orders of magnitude, to unveil the accretion mechanism in these galaxies. We estimate the accretion rate of gas associated with their hot coronae by analyzing archival Chandra data, to derive the deprojected density and temperature profiles in a spherical approximation. Measuring the jet power from the nuclear radio-luminosity, we find that the accretion power correlates linearly with the jet power,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
154
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 118 publications
(178 citation statements)
references
References 47 publications
23
154
1
Order By: Relevance
“…In agreement with previous studies (e.g. Best et al 2005;Mauch & Sadler 2007), in the Virgo cluster the detection of a radio source is also highly favored in more massive galaxies. The nine VCC/CoreG have similar masses, all within the range 10 11 −10 12 M .…”
Section: The Samplesupporting
confidence: 92%
“…In agreement with previous studies (e.g. Best et al 2005;Mauch & Sadler 2007), in the Virgo cluster the detection of a radio source is also highly favored in more massive galaxies. The nine VCC/CoreG have similar masses, all within the range 10 11 −10 12 M .…”
Section: The Samplesupporting
confidence: 92%
“…Eracleous et al (2010) reported an Eddington ratio of 4 × 10 −4 , indicating inefficient SMBH accretion well below the Eddington luminosity, consistent with the classification of NGC 3998 as a Low Excitation Radio Galaxy (LERG; Best & Heckman 2012). The inefficient accretion characteristic of LERGs may be driven by gas cooling from the hot galactic halo supplying fuel to the SMBH via Bondi accretion (Croton et al 2006;Allen et al 2006;Hardcastle et al 2007;Balmaverde et al 2008), or perhaps by chaotic accretion of turbulent clouds (e.g., Gaspari et al 2015, and references therein).…”
Section: Energetics and Triggeringmentioning
confidence: 54%
“…Hence, they will fade away on relatively short timescales, therefore explaining the rarity of low surface brightness radio lobes in galaxies like NGC 3998. 6 We emphasize that this is only a rough estimate since the intrinsic scatter in both the P jet − P radio and P jet − P acc relation are both ∼0.7 dex (Balmaverde et al 2008;Cavagnolo et al 2010;Nemmen & Tchekhovskoy 2015).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Bondi accretion has been suggested by several studies (Croton et al 2006;Allen et al 2006;Hardcastle et al 2007;Balmaverde et al 2008). Taking the core luminosity measured by Liuzzo et al (2010) and following the reasoning of Balmaverde et al (2008), connecting the radio core luminosity to the radio jet power and relating that to the Bondi accretion power (P B = 0.1Ṁc 2 ), we estimate that the accretion rate of 4C 35.06 is on the order of 0.2 M yr −1 . If part of the detected H I is associated with infalling gas (something possible given the width of the profile that also spans to redshifted velocities) it could provide the required fueling material.…”
Section: Presence Of Cold Gasmentioning
confidence: 65%